Analysis of Crack Propagation in Carbon Nanotube Reinforced Magnesium Based Composites Under Tensile Load - Zhou, Shuang; Tian, Xu; Xie, Ying (International Journal of Materials Science and Technology Studies, 2024)
This article mainly conducts numerical simulations on the crack propagation of carbon nanotube reinforced magnesium based composites during uniaxial tensile failure. Selecting the cross-section of a representative carbon nanotube reinforced magnesium based composite material model as the research object, the model was loaded in multiple load steps using ANSYS finite element software, and the location and propagation path of cracks were discussed. It was found that cracks first appeared at the interface between carbon nanotubes and magnesium matrix; The direction of crack propagation is perpendicular to the direction of the load, which is called vertical crack propagation; As the load step gradually increases, the crack propagation speed gradually increases, especially when two parallel vertical cracks overlap, the crack propagation speed becomes more significant; Throughout the entire crack propagation process, the matrix has the most damaged units.